Electrochemical performance of barium strontium cobalt ferrite - samarium doped ceria - argentum for low temperature solid oxide fuel cell - Asyikin Yusop, Umira; Kang Huai, Tan; Abd.Rahman, Hamimah; Baharuddin, Nurul Akidah; Raharjo, Jarot (2020)
A low operating temperature is one of the concerns in commercialising solid oxide fuel cells (SOFCs) as a portable power source. The aim of this research is to develop a new cathode material, barium strontium cobalt ferrite–samarium doped ceria (BSCF-SDC) added with argentum (Ag) for low-temperature SOFCs (LT-SOFCs). The composite powder was prepared through highenergy ball milling at 550 rpm for 2 h with a BSCF:SDC powder ratio of 50:50. The composite powder was calcined at 950 °C for 2 h and then mixed with Ag (1wt%, 3wt% and 5wt%) via dry milling at 150 rpm. The phase stability of the resulting samples was examined by X-ray diffractometry, and powder particle sizes were determined by using a Zeta-Sizer Nano ZS. The thermal stability of each sample was determined on the basis of thermal expansion coefficients (TECs), and electrochemical characteristics were determined through electrochemical impedance spectroscopy to investigate the performance of BSCF-SDC-Ag in LT-SOFCs (400–600 °C). Phase analysis demonstrated no impurity phases existed. Particle size analysis revealed that increment in Ag content affect the particle size of BSCF-SDCC. TEC analysis demonstrated that BSCF-SDCAg1% has a mismatch value of 16.39%, which is within the acceptable TEC range of 15%–20%. BSCF-SDC-Ag1% showed a maximum conductivity of 39.37Scm-1 at 600 °C.